Psychogenic alopecia in felines: Literature review (Research, Society and Development, 2024)
Psychogenic alopecia in felines is a dermatological condition of behavioral origin, characterized by hair loss due to excessive licking, generally associated with stress and anxiety. This work aims to carry out a literature review on psychogenic alopecia, addressing its main risk factors, diagnosis and forms of treatment. The condition is often diagnosed by exclusion, after eliminating organic causes such as parasitic infections, dermatitis and allergies. Environmental factors, such as changes in the family environment, territorial conflicts and lack of environmental enrichment, are common triggers of this disorder. Therapeutic interventions include changes in the environment, behavioral techniques, and the use of psychotropic drugs such as fluoxetine and clomipramine. Effective management requires a multidisciplinary approach, involving both environmental modifications and drug therapies, with the aim of improving the quality of life of affected felines. The study highlights the importance of early diagnosis and the implementation of personalized strategies for each case, considering the interactions between behavioral and emotional factors.